Exploring the structural controls on helium, nitrogen and carbon isotope signatures in hydrothermal fluids along an intra-arc fault system. (1st July 2016) - Tardani, Daniele; Reich, Martin; Roulleau, Emilie; Takahata, Naoto; Sano, Yuji; Pérez-Flores, Pamela; Sánchez-Alfaro, Pablo; Cembrano, José; Arancibia, Gloria
Abstract: There is a general agreement that fault-fracture meshes exert a primary control on fluid flow in both volcanic/magmatic and geothermal/hydrothermal systems. For example, in geothermal systems and epithermal gold deposits, optimally oriented faults and fractures play a key role in promoting fluid flow through high vertical permeability pathways. In the Southern Volcanic Zone (SVZ) of the Chilean Andes, both volcanism and hydrothermal activity are strongly controlled by the Liquiñe-Ofqui Fault System (LOFS), an intra-arc, strike-slip fault, and by the Arc-oblique Long-lived Basement Fault System (ALFS), a set of transpressive NW-striking faults. However, the role that principal and subsidiary fault systems exert on magma degassing, hydrothermal fluid flow and fluid compositions remains poorly constrained. In this study we report new helium, carbon and nitrogen isotope data ( 3 He/ 4 He, δ 13 C–CO2 and δ 15 N) of a suite of fumarole and hot spring gas samples from 23 volcanic/geothermal localities that are spatially associated with either the LOFS or the ALFS in the central part of the SVZ. The dataset is characterized by a wide range of 3 He/ 4 He ratios (3.39 Ra to 7.53 Ra, where Ra = ( 3 He/ 4 He)air ), δ 13 C–CO2 values (−7.44‰ to −49.41‰) and δ 15 N values (0.02‰ to 4.93‰). The regional variations in 3 He/ 4 He, δ 13 C–CO2 and δ 15 N values are remarkably consistent with those reported for 87 Sr/ 86 Sr in lavas along the studied segment, which are strongly controlled by the regional spatial distribution of faults. Two fumaroles gas samples associated with the northern "horsetail" transtensional termination of the LOFS are the only datapoints showing uncontaminated MORB-like 3 He/ 4 He signatures. In contrast, the dominant mechanism controlling helium isotope ratios of hydrothermal systems towards the south appears to be the mixing between mantle-derived helium and a radiogenic component derived from, e.g., magmatic assimilation of 4 He-rich country rocks or contamination during the passage of the fluids through the upper crust. The degree of 4 He contamination is strictly related with the faults controlling the occurrence of volcanic and geothermal systems, with the most contaminated values associated with NW-striking structures. This is confirmed by δ 15 N values that show increased mixing with crustal sediments and meteoric waters along NW faults (AFLS), while δ 13 C–CO2 data are indicative of cooling and mixing driving calcite precipitation due to increased residence times along such structures. Our results show that the structural setting of the region exerts a fist-order control on hydrothermal fluid composition by conditioning residence times of magmas and thus promoting cooling/mixing of magmatic vapor, and therefore, must be taken into consideration for further geochemical interpretations.